Recognition of language barriers in comprehending non-communicable disease management among rural elderly people in the DIMAMO surveillance area: a case of AWI-Gen participants - Reneilwe G Mashaba; Kagiso P Seakamela; Masenyani O Mbombi; Livhuwani Muthelo; Precious M Makoti; Solomo SR Choma; Eric Maimela; Cairo B Ntimana (BMC Public Health, 2024)
Abstract Background Language plays a critical role in health communication, particularly in the management and understanding of non-communicable diseases (NCDs) among elderly populations. This study aimed to explore the language barriers that affect elderly participants’ comprehension of NCDs, focusing on how these barriers impact their understanding of disease causes, symptoms, treatment, and self-management. The study also investigated how linguistic differences between healthcare workers and patients influence the effectiveness of health interventions in a rural South African context. Methods This qualitative phenomenological study was conducted with elderly participants aged 60 years and above, all of whom have chronic diseases. In-depth face-to-face interviews were conducted using an interview guide during the AWI-Gen 2 research feedback sessions in the Ga-Dikgale area. Data analysis was performed using QSR NVivo 10 to identify key themes. Results Five major themes emerged regarding participants’ understanding of NCDs and the perceived language barriers. These include Limited Knowledge and Awareness of NCDs, Misconceptions about NCDs, Mixed perceptions regarding NCD causes and treatment, Discrepancies in healthcare workers’ communication, and the Importance of interpreters in facilitating NCD-related communication. Conclusion The study revealed significant misconceptions about diabetes and hypertension, as well as traditional practices like bloodletting, which were perceived to relieve hypertension symptoms. It also identified critical communication barriers, including limited time for health practitioners to explain diagnoses and treatments. The findings emphasize the need for interpreters and culturally sensitive communication strategies to improve health literacy and care. Collaborative efforts between traditional and western health practitioners are recommended to address these issues and enhance community health interventions.